A Prospective, Randomized, Multicenter, Open-label Clinical Trial Comparing Intradiscal Biacuplasty to Conventional Medical Management for Discogenic Lumbar Back Pain. Issue 13 (July 2016) - Desai, Mehul J.; Kapural, Leonardo; Petersohn, Jeffrey D.; Vallejo, Ricardo; Menzies, Robert; Creamer, Michael; Gofeld, Michael
Abstract : Study Design: This study was a prospective, randomized, crossover, multicenter trial for the evaluation of comparative effectiveness of intradiscal biacuplasty (IDB) versus conventional medical management (CMM) in the treatment of lumbar discogenic pain. Objective: The objective was to demonstrate the superiority of IDB over CMM in the treatment of discogenic pain with respect to the primary outcome measure. Summary of Background Data: Current therapeutic options for the treatment of chronic low back pain of discogenic origin are limited. CMM is often unsatisfactory with regard to the treatment of discogenic pain. IDB offers a minimally invasive treatment that has been demonstrated to be superior to placebo in the past. Methods: A total of 63 subjects with lumbar discogenic pain diagnosed via provocation discography were randomized to IDB + CMM (n = 29) or CMM-alone (n = 34). At 6 months, patients in the CMM-alone group were eligible for crossover if desired. The primary outcome measure was the change in visual analog scale (VAS) from baseline to 6 months. Secondary outcome measures included treatment "responders, " defined as the proportion of subjects with a 2-point or 30% decrease in VAS scores. Other secondary measures included changes from baseline to 6 months in (1) short form (SF) 36-physical functioning, (2) Oswestry Disability Index, (3) Beck Depression Inventory, (4) Patient Global Impression of Change, (5) EQ-5D VAS, and (6) back pain-related medication usage. Results: In the IDB cohort, the mean VAS score reduction exceeded that in the CMM cohort (−2.4 vs. −0.56; P  = 0.02), and the proportion of treatment responders was substantially greater (50% vs. 18%). Differences in secondary measures favored IDB. No differences in opioid utilization were noted between groups. Conclusion: Superior performance of IDB with respect to all study outcomes suggests that it is a more effective treatment for discogenic pain than CMM-alone. Level of Evidence: 2